Evaluation of antibacterial potential of biosurfactant produced by surfactin-producing Bacillus isolated from selected Malaysian fermented foods - Mohd Hafez Mohd Isa; Shamsudin N.H.; Al-Shorgani N.K.N.; Alsharjabi F.A.; Kalil M.S. (Taylor and Francis Inc., 2024)
Indexed by WOS/Scopus/ERA